Advanced-Level EFL Students’ Perception on Wordwall in Vocabulary Learning - Muhammad Bahauddin; Mustofa, Mutmainnah (Universitas Cokroaminoto Palopo, 2025)
This study investigated the impact of Wordwall, an interactive learning platform, on student vocabulary acquisition and class room engagement. Student perceptions were gauged through a series of statements reflecting their experiences using Wordwall. Overwhelmingly, students reported positive feelings towards Wordwall, describing it as exciting, interesting, motivating, and fun. They found it enhanced their learning experience by making vocabulary learning easier and contributing to a more energetic classroom atmosphere. The quantitave descriptive research design is used collect and analyze the data. The findings suggest that incorporating Wordwall into vocabulary instruction can significantly increase student engagement and potentially improve vocabulary acquisition. Further research can explore the platform's impact on diverse learning styles and its long-term effects on vocabulary retention.